Popular Songs in the English Classroom in Czech Lower-Secondary and Secondary Education - Zitková, Helena; Vít, Marek (My University, 2016)
We believe that popular songs in ELT have great potential. While they are accessible and easy to work with (Murphey, 1992), they may help to develop all aspects of communicative competence (linguistic, socio-linguistic and pragmatic according to CEFR, 2001) and, at the same time, involve all learning domains, i.e. cognitive, affective and psychomotor (Anderson; Krathwohl 2001; Bloom; Krathwohl 1964; Dave 1967). To find out whether the potential of popular songs might be fully exploited in ELT, we carried out a research the aim of which was to survey the situation in Czech lower-secondary and secondary English classrooms. The findings are presented in our paper.
Populární písně v hodinách anglického jazyka na II. stupni českých základních škol a na středních školách
Keywords: music in ELT; communicative competence; learning domains; hudba ve výuce anglického jazyka; komunikační kompetence; domény učení